Ultrastructural changes of hemocapillaries of the lungs in the late development of experimental acute pancreatitis - Zaiats, Liubomyr; Pasichnyk, Olga; Zukow, Walery (Journal of Education, Health and Sport, 2024)
Background. Today, acute pancreatitis is a common form of acute abdomen in the clinic, the incidence of which has been increasing in recent years. The aim of the work was to study the dynamics of ultrastructural changes of the hemocapillaries of the alveolar wall of the lungs in the late stages of experimental acute pancreatitis. Material and methods. The experiments were carried out on 54 white Wistar male rats weighing 180–220 g. The animals were divided into three groups: first — intact, second — control, third — experimental with a model of acute pancreatitis, which was reproduced by intraperitoneal administration of a 20% solution of L-arginine at a total dose of 5 g/kg at one-hour interval. The control group of animals was intraperitoneally injected with an equivalent dose of isotonic sodium chloride solution. All research were performed under sodium thiopental anesthesia at the rate of 60 mg/kg body weight. Lung tissue for electron microscopic examination was collected from the lower lobe of the left lung at 3–5 and 7 days. Pieces of lung tissue measuring 1×1×1 mm were fixed in a 2.5% glutaraldehyde solution, followed by additional fixation in a 1% osmium tetroxide solution. After dehydration, the material was poured into Epon-Araldite. Sections with a thickness of 20–50 nm obtained on “Tesla BS-490” ultramicrotome were studied in a PEM-125K electron microscope. Results. The ultrastructural analysis showed that already 3 days after the study, dystrophic-destructive changes, as well as adhesion and aggregation of leukocytes, were detected in the endothelial cells. As the study period increased (5–7 days), the intensity of changes in the hemocapillaries of the alveolar wall increased significantly. In the lumen erythrocyte sludge, thromboleukocyte adhesion and aggregation are determined in hemocapillaries. Conclusion. Acute experimental pancreatitis is accompanied by marked changes in the ultrastructural structure of hemocapillaries of the alveolar wall. The nature and severity of structural changes in the hemocapillaries of the alveolar wall depends on the duration of the course of arginine-induced acute pancreatitis.